Structural and functional insights into the mechanism of action of plant borate transporters - Savvas Saouros (Nature Portfolio, 2021)
Abstract Boron has essential roles in plant growth and development. BOR proteins are key in the active uptake and distribution of boron, and regulation of intracellular boron concentrations. However, their mechanism of action remains poorly studied. BOR proteins are homologues of the human SLC4 family of transporters, which includes well studied mammalian transporters such as the human Anion Exchanger 1 (hAE1). Here we generated Arabidopsis thaliana BOR1 (AtBOR1) variants based (i) on known disease causing mutations of hAE1 (S466R, A500R) and (ii) a loss of function mutation (D311A) identified in the yeast BOR protein, ScBOR1p. The AtBOR1 variants express in yeast and localise to the plasma membrane, although both S466R and A500R exhibit lower expression than the WT AtBOR1 and D311A. The D311A, S466R and A500R mutations result in a loss of borate efflux activity in a yeast bor1p knockout strain. A. thaliana plants containing these three individual mutations exhibit substantially decreased growth phenotypes in soil under conditions of low boron. These data confirm an important role for D311 in the function of the protein and show that mutations equivalent to disease-causing mutations in hAE1 have major effects in AtBOR1. We also obtained a low resolution cryo-EM structure of a BOR protein from Oryza sativa, OsBOR3, lacking the 30 C-terminal amino acid residues. This structure confirms the gate and core domain organisation previously observed for related proteins, and is strongly suggestive of an inward facing conformation.